RAPID IDENTIFICATION OF CLIMATE CHANGE IMPACTS ON THE WEST TARUM CHANNEL - Dahlia, Lia; Suryadi, Yadi; Nugroho, Eka; Chaidar, Ana Nurganah; Hatmoko, Waluyo (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
There is no doubt that El Niño and La Niña phenomena, which are characterized by sea surface temperature (SST) anomalies in the equatorial Pacific Ocean, have significant impacts on global and regional climate. The Oceanic Niño Index (ONI), obtained from NOAA satellite imagery, is used to measure these SST anomalies. El Niño is characterized by an increase in sea surface temperature of more than 0.5°C above normal, while La Niña is characterized by a decrease in sea surface temperature of more than 0.5°C below normal. The strength of the anomaly determines whether the phenomenon is weak, moderate, strong, or very strong. El Niño and La Niña events cause various hydrometeorological disasters that directly impact rainfall and water availability. The Indonesian Maritime Continent, located between oceans, is particularly vulnerable to the impacts of these two phenomena. El Niño causes drought, while a positive ONI increases the intensity of rainfall. These phenomena have the potential to reduce rainfall, disrupt water supply, and exacerbate droughts by changing global weather patterns. This study will identify the impacts of El Niño events on rainfall and water availability in the West Tarum Canal, which covers Karawang, Bekasi, and parts of Jakarta. By understanding these impacts, we can develop effective adaptation strategies. A literature review will provide a comprehensive picture of rainfall and water availability in the era of climate change by analyzing data from previous studies.